Penguatan Nilai Moderasi Beragama Anak Usia Dini Melalui Edukasi Lingkungan Berbasis Tanaman Obat Keluarga - Muslimah Muslimah; Ahmadi Ahmadi; Selvi Wulandari (Jurnal Pengabdian Kepada Masyarakat, 2026)
Strengthening religious moderation values in early childhood is essential for developing tolerant, inclusive, and harmonious character in a plural society. This community service study aims to describe the implementation of religious moderation values through environmental education based on Family Medicinal Plants (TOGA) in Margokoyo Village, Belitang Jaya District, OKU Timur Regency, targeting local early childhood children as partners. A qualitative descriptive method was employed through the stages of preparation, training and guidance in planting, evaluation, and final reinforcement. Data were collected through observation and documentation at each stage of the program. The results indicate that TOGA activities not only enhance knowledge about medicinal plants but also internalize religious moderation values, including cooperation, tolerance, mutual respect, and environmental care. Children demonstrated high enthusiasm and positive interactions without distinguishing religious or cultural backgrounds. Environmental education based on TOGA proves to be a contextual, enjoyable, and effective learning medium for instilling religious moderation values from an early age, while also equipping children to live harmoniously in a diverse society.